A novel UHPFRC-based protective structure for bridge columns against vehicle collisions: Experiment, simulation, and optimization. (15th March 2020) - Fan, Wei; Shen, Dongjie; Zhang, Zhiyong; Huang, Xu; Shao, Xudong
Highlights: A novel UHPFRC-based protection was proposed to protect bridge columns against vehicle collisions and to reduce vehicle damage and casualties. Drop-hammer impact tests were performed to investigate the impact behaviors of CST-UHPFRC composite structures. An FE modeling method considering manufacture process was proposed and validated for predicting the impact responses. A multi-objective optimization procedure was developed for the design of the proposed protective structures. Abstract: The paper aims to develop a new protective structure based on ultra-high performance fiber reinforced concrete (UHPFRC) to protect bridge columns against vehicle collisions and to reduce vehicle damage and casualties. The drop-hammer impact tests were performed to investigate the response of the composite structure composed of UHPFRC panels and the energy-absorbing member of corrugated steel tubes. For all test specimens, the expected damage modes were observed during impact testing. Specifically, the energy-absorbing member experienced large deformation to dissipate the kinetic energy of drop hammer, while slight damages occurred in the UHPFRC panels directly contacted with a drop hammer. Also, the impact tests showed that the impact force was more sensitive to the number of corrugated tubes than the tube thickness. On the contrary, increasing the tube thickness more effectively improved the energy dissipation capacity of the structure than adding the number of corrugated steel tubes. A finite element (FE) modeling method considering manufacturing process was proposed and demonstrated to be capable of capturing the impact-induced response of UHPFRC-based composite structures. Comparisons between the experimental data and the numerical results highlighted the importance of including the influence of the manufacturing process in modeling corrugated steel tubes. Using the validated FE modeling method, two types of UHPFRC-based protective structures were investigated and compared. Results showed that the protective structure with disconnection details between inner and outer panels was superior to that with connection details. The advantages of the former one included more effective reductions of the impact force and damage in UHPFRC panels for the reuse to improve the economy. Finally, a multi-objective optimization design procedure was presented to find the optimum configuration of the proposed protective structures under vehicle collisions.